2009
DOI: 10.1021/es9014019
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Organophosphate Flame Retardants in Furniture Foam and U.S. House Dust

Abstract: Restrictions on the use of polybrominated diphenyl ethers (PBDEs) have resulted in the increased use of alternate flame retardant chemicals to meet flammability standards. However, it has been difficult to determine which chemical formulations are currently being used in high volumes to meet flammability standards since the use of flame retardant formulations in consumer products is not transparent (i.e. not provided to customers). To investigate chemicals being used as replacements for PentaBDE in polyurethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

22
472
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 698 publications
(499 citation statements)
references
References 38 publications
22
472
5
Order By: Relevance
“…1 Environmental monitoring demonstrated that TDCPP was present in more than 96% of the indoor dust samples examined in the United States, with concentrations ranging from <90 ng/g to 56 μg/g. 4 Higher concentrations of TDCPP (mean = 130 μg/g) were detected in car dust in Germany. 5 These data suggest that human exposure to TDCPP might commonly occur in some areas.…”
Section: ■ Introductionmentioning
confidence: 92%
“…1 Environmental monitoring demonstrated that TDCPP was present in more than 96% of the indoor dust samples examined in the United States, with concentrations ranging from <90 ng/g to 56 μg/g. 4 Higher concentrations of TDCPP (mean = 130 μg/g) were detected in car dust in Germany. 5 These data suggest that human exposure to TDCPP might commonly occur in some areas.…”
Section: ■ Introductionmentioning
confidence: 92%
“…Due to the adverse health effects caused by brominated flame retardants, such as polybrominated diphenyl ethers (PBDEs), many industrial countries have banned or phased-out PBDEs, and OPFRs have been proposed as alternatives (Stapleton et al, 2009). Consequently, the production and usage of OPFRs has increased and now they are ubiquitous environmental contaminants and they are also detectable in biota samples (Stapleton et al, 2009;van der Veen and de Boer, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the OPs are directly mixed into the materials and are not chemically bonded; therefore, they can be easily released or leached into the surrounding environment from the OP-containing products during manufacture, application, or disposal [4]. Their widespread application has resulted in extensive diffusion and ubiquitous distribution in the environment, for example, in air [8][9][10][11], wastewater and sludge [12][13][14], surface water [6,13,[15][16][17], groundwater [1], sediment [18][19][20], soil [7], and even the human body [21][22][23].…”
Section: Introductionmentioning
confidence: 99%